A Critical Reading of Modern Arabic Linguistics through the Book Modern Arabic Linguistics: A Critical Study of Sources and Theoretical Foundations by Mustafa Ghali Fane - saad, Amar; guerfa, zina (El Omda in Linguistics and Discourse Analysis, 2025)
The reality of linguistic research among contemporary Arab linguists is confused and lacks clear boundaries, despite numerous studies that have attempted to enrich this field. Among these efforts is the work of Dr. Mustafa Ghali Fane, who argues that most Arab linguists have not yet fully understood the nature and function of linguistics. He also maintains that many Arab studies have remained at the margins of linguistics and have not reached its core essence. Accordingly, this article seeks to shed light on the nature of modern Arabic linguistic writing according to Mustafa Ghali Fane’s perspective, and to examine how he criticizes modern Arabic linguistics in terms of both methodology and practice.